Distributions of Transposable Elements Reveal Hazardous Zones in Mammalian Introns - Zhang, Ying; Romanish, Mark T.; Mager, Dixie L. (PLOS Computational Biology, 2011)
Author Summary Sequences derived from transposable elements (TEs) are major constituents of mammalian genomes and are found within introns of most genes. While nearly all TEs within introns appear harmless, some de novo intronic TE insertions do disrupt gene transcription and splicing and cause disease. It is unclear why some intronic TEs perturb gene transcription whereas most do not. Here, we examined intronic TE distributions in both human and mouse genes to gain insight into which TEs may be more likely to affect transcription. We found evidence that TEs near exons are likely subject to strong negative selection but the size of the region under selection or “underrepresentation zone” differs for different TE classes. Strikingly, all reported human disease-causing intronic TE insertions fall within these underrepresentation zones, and the proportion of TEs contributing to chimeric TE-gene transcripts is significantly higher when TEs are located in these zones. We also examined insertionally polymorphic mouse TEs located within underrepresentation zones and found evidence of transcriptional disruption in two genes. Given the growing appreciation for ongoing activity of TEs in human, our results should be of value in prioritizing insertionally polymorphic TEs for study of their potential contributions to gene expression differences and phenotypic variability.